Arthroplasty A Comprehensive Review - Bagaria, Vaibhav (IntechOpen, 2016)
This book is aimed at giving an overview of the field of arthroplasty and covers arthroplasty of several regions starting from the cervical spine to the ankle. While the current trend is focusing on one particular joint, sometimes having an understanding of the entire subject and cross learning from various subspecialties play a key role in evolving the science. The book is precisely meant to do that, exposing the readers to various types of arthroplasties. It also touches on failures and complications like infections to ensure that the subject is dealt with in a comprehensive manner. Radiology and investigations form an important element for successful outcomes and so does being informed about the newer developments in the field. The chapters on 3D printing and PRP ensure that the all the subjects from the very basic to what can be expected on the horizon are well covered.